2006
DOI: 10.1038/nsmb1160
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for ubiquitin recognition by the human ESCRT-II EAP45 GLUE domain

Abstract: The ESCRT-I and ESCRT-II complexes help sort ubiquitinated proteins into vesicles that accumulate within multivesicular bodies (MVBs). Crystallographic and biochemical analyses reveal that the GLUE domain of the human ESCRT-II EAP45 (also called VPS36) subunit is a split pleckstrin-homology domain that binds ubiquitin along one edge of the beta-sandwich. The structure suggests how human ESCRT-II can couple recognition of ubiquitinated cargoes and endosomal phospholipids during MVB protein sorting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 14 publications
1
59
0
Order By: Relevance
“…Previous studies suggested that ubiquitylation of certain membrane proteins is a very critical signal for its sorting into intraluminal vesicles (ILVs) of endosomes, then MVBs (Henne et al, 2011;Marchese et al, 2008;Raiborg and Stenmark, 2009). In addition, in yeast and mammalian cells, Vps36 can recognize the ubiquitylated proteins (Alam et al, 2006;Hirano et al, 2006;Teo et al, 2006). In the experiment, we found that Vps36 recognizes Smo in the absence of Hh, but not in yeast two-hybrid assay.…”
Section: The Ubiquitin Signal Mediates the Interaction Between Smo Anmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies suggested that ubiquitylation of certain membrane proteins is a very critical signal for its sorting into intraluminal vesicles (ILVs) of endosomes, then MVBs (Henne et al, 2011;Marchese et al, 2008;Raiborg and Stenmark, 2009). In addition, in yeast and mammalian cells, Vps36 can recognize the ubiquitylated proteins (Alam et al, 2006;Hirano et al, 2006;Teo et al, 2006). In the experiment, we found that Vps36 recognizes Smo in the absence of Hh, but not in yeast two-hybrid assay.…”
Section: The Ubiquitin Signal Mediates the Interaction Between Smo Anmentioning
confidence: 65%
“…The GLUE domain interacts with 3-phosphorylated phosphoinositides and one of the NZF domains is responsible for recognizing ubiquitin (Teo et al, 2006). However, the GLUE domain rather than the NZF domain, has been found in the mammalian and Drosophila homologs of Vps36 (Alam et al, 2006;Hirano et al, 2006;Irion and St Johnston, 2007;Slagsvold et al, 2005). To test whether the Drosophila Vps36 GLUE domain plays a role in Smo interaction with Vps36, we performed additional Co-IP experiments.…”
Section: Vps36 Interacts With Smo In the Absence Of Hh Signalmentioning
confidence: 99%
“…The PHD fold of Pru domain from Rpn13 subunit of proteasome binds the common hydrophobic pocket of Ub through exclusive loops (35,36). However, the GLUE domain from ESCRT-II EAP45 binds the Ile 44 -containing surface of Ub through the residues within secondary structural elements including C-terminal helix (37), although it also adopts a PHD fold.…”
Section: Discussionmentioning
confidence: 99%
“…Both Vps23 and Tsg101 bind Ub similarly, using a Ub E2 variant (UEV) domain ,Teo et al 2004b. Mammalian Vps36/EAP45 uses a GLUE domain to bind both phosphorylated phosphatidylinositols and Ub (Alam et al 2006,Hirano et al 2006,Teo et al 2006. Several residue differences in the yeast Vps36 GLUE domain are predicted to prevent its Ub binding.…”
Section: Lumen Ubiquitin As a Sorting Signalmentioning
confidence: 99%